Socio-Economic Condition and Occupation Migration of Fisherman of the Jamuna River under Shirajgonj District in Bangladesh - Rahman, K.M.M; Naher, M; Adhikary, R.K.; Khan, N.S.; Rahman, Mohammad Mustafizur; Assadujjaman, M; A Rahman, M (IDOSI Publications, 2014)
A field study was conducted on the socio-economic condition of the fishermen community, occupation migration and fish biodiversity in the Jamuna River at Belkuchi char areas under Shirajgonj district, Bangladesh. The study was conducted from November 2012 to August 2013. Data were collected from randomly selected 100 respondents of fishermen community using semi-structured questionnaire interview and Focus Group Discussion (FGD). Fish biodiversity data were also collected from four major markets. The result was calculated by collecting present data and 15 years ago data from the interviewers. The study indicated that most of the fishermen had improved their average annual income, housing condition, drinking water facility, sanitation facility, health facility etc. The fishermen are adapting to different occupations beside fishing such as fish culture, fish selling, agriculture, boat making, labor, looming, business, CNG driving and migration to town for seeking seasonal jobs. A significant amount of fishermen (30%) are adapting to these different livelihood options. Only 8% fishermen got subsidy in the study area. The main problems are extortion by the local extortionists, inadequate credit, lack of appropriate gear etc. A total of 57 species of fishes under 20 families and 9 orders were found in the Jamuna River. The study recommends that governmental and nongovernmental organizations should help the fishermen in adapting their livelihood in different sector during banning season. Government should also monitor the subsidy facility carefully till reaching the true fishermen. Besides, these organizations should also help in conserving the fish diversity of the Jamuna River to reduce the vulnerability of fishermen.